Trilobites and graptolites from the Vargas Peña Formation (Early Silurian), Paraná Basin, eastern Paraguay - Tortello, Marcelo Franco (2012)
Early Silurian trilobites and graptolites from the Vargas Peña Formation of the western Paraná Basin are described. The studied material comes from two successions (San Fernando and Galeano quarries) on the southwestern fank of the Ypacaraí graben, about 30 km southeast of Asunción city, eastern Paraguay. The faunas include Calymene boettneri Harrington, C. harringtoni tortello sp. nov., Trimerus sp., Dalmanites ypacarayensis (BalDis & Hansen), Dalmanites sp., Guaranites paraguayensis BalDis & Hansen, Eophacops sp., Normalograptus cf. ajjeri (legranD), N. aff. rectangularis (mccoy), Metaclimacograptus cf. asejradi legranD, Paraclimacograptus innotatus (nicHolson), and P. brasiliensis (rueDemann). The taxa recognized suggest a ?late Rhuddanian to late Aeronian/early Telychian age for the Vargas Peña Formation. The graptolites constitute a low diversity, oxygen tolerant fauna that would be indicative of shallow water conditions, an environment that is also supported by the occurrence of the trilobite genus Trimerus.